The relationship of chronic energy deficiency (CED), exclusive breastfeeding, and economic with stunting in Nagari Aua Kuning West Pasaman - Wiwie Putri Adila; Roza Sri Yanti; Mayetti (Science Midwifery, 2023)
Stunting is a chronic malnutrition problem caused by poor nutritional intake, repeated infections, and inadequate psycho-social stimulation at the first 1000 days of life, characterized by height for age below the applicable standard, Prevalence of stunting in Indonesia in 2019 was 27.7%. In 2021 it became 24.4%, and although it has decreased, Indonesia is still far from the target. Objective: This study aims to determine the relationship between CED, exclusive breastfeeding, and economic status with the incidence of stunting in children. This research is an observational analytic study with a cross-sectional design. A total of 224 respondents were selected randomly by proportional random sampling, and the study was conducted in July-September 2022. Data collection was carried out by measuring height, looking at the MCH book, interviews, and questionnaires. Bivariate analysis was performed using chi-square and multivariate using multiple logistic regression. The results showed that 50.9% of children are stunted. Chi-square results show a significant relationship between the history of CED with a p-value of 0.000, exclusive breastfeeding with a p-value of 0.020, and economic status with a p-value of 0.003 and the incidence of stunting. CED is the most dominant factor affecting the incidence of stunting. Statistically, CED has a risk of 11.278 times, affecting the occurrence of stunting. This study suggests Health agencies and related parties to collaborate in early detection, reduce the risk of stunting, and be able to run programs that the government has made.